The Economic Prospects of Fisher-Laborers Amidst Climate Dynamics: From Vulnerability to Decent Conditions (Case Study of Tambakrejo Fishers, Semarang City) - Indah Susilowati; Siti Nur Arofah; Hira Davika; Silviana Ika Susanti (International Journal of Economics, Business and Innovation Research, 2026)
The fisheries sector plays a crucial role in global economic development, particularly for food security and the well-being of coastal communities. It is a cornerstone of national economic development for citizens whose economic growth depends on the primary sector. In the context of fisheries, vulnerability arises from a combination of biophysical factors such as increased frequency of natural disasters, extreme weather changes, and oceanographic dynamics, all of which are beyond human control. Tropical coastal ecosystems are experiencing significant ecological stress as a direct consequence of atmospheric warming. The economic vulnerability of coastal communities is not only triggered by environmental aspects due to climate change, but is also caused by socio-economic factors, institutional access, fishing technology, and local social structures, which either strengthen or weaken the level of vulnerability. The environmental, social, and economic aspects of Tambakrejo fishing laborers' susceptibility might also be examined. The first objective is to explore the resources found in the waters of Tambakrejo; the second objective is to identify fishermen's perceptions of the factors that make them vulnerable; and the third objective is to identify the adaptive capacity of fishermen.The qualitative approach was conducted thru simple triangulation with the assistance of the ATLAS.ti software to address the fourth research objective, which is to analyze strategies that enable fishermen to improve their conditions from vulnerable to sustainable. This research uses primary and secondary data. The respondents in this study consisted of 30 fishermen selected using purposive sampling technique.